A group of genes required for pattern formation in the ventral ectoderm of the Drosophila embryo. - Mayer, U.; Nusslein-Volhard, C. (Genes & Development, 1988)
Mutations in the genes spitz (spi), Star (S), single-minded (sim), pointed (pnt), rhomboid (rho) (all zygotic), and sichel (sic) (maternal), collectively called the spitz group, cause similar pattern alterations in ventral ectodermal derivatives of the Drosophila embryo. The cuticle structures lacking in mutant embryos normally derive from longitudinal strips of the ventro-lateral blastoderm. Defects were found in the median part of the central nervous system in whole-mount embryos stained with anti-HRP (horseradish peroxidase) antibodies. In addition, the nerve cells expressing the even-skipped protein appeared abnormally arranged. These results suggest that groups of cells from the same region, including both epidermal and neural precursor cells, require spitz-group gene activity for normal development. The members of the spitz group differ from one another: sim affects a more median strip of the ventral ectoderm than the other zygotic genes and pnt causes separation rather than deletion of pattern elements. As shown by pole cell transplantations, spi and S are also required for normal development of the female germ line, while sim, rho, and pnt appear to be exclusively zygotically expressed, and the maternal gene sic acts in the germ line autonomously. Some embryos produced by sic-homozygous females differentiate the spitz phenotype, others develop normally or die early. Of all the spitz-group genes, sim appears to have the most specific effect on the embryonic pattern. The significance of the spitz-group phenotypes for the dorso-ventral pattern formation is discussed.